Labor Market Developments During Economic Transition - Rutkowski, Jan (World Bank, Washington, DC, 2012)
The paper reviews labor market developments in the transition economies of Europe and Central Asia. It argues that the scarcity of productive job opportunities and the growing labor market segmentation are the two main labor market problems facing the transition economies. In the European transition economies the lack of jobs has led to persistent open unemployment. In the Commonwealth of Independent States (CIS) it has led to hidden unemployment (underemployment and low productivity employment). Unemployment in the European transition economies is supported by the developed social safety net. In contrast, in the CIS for most workers unemployment is not an affordable option. They either stick to their old, unproductive jobs in unrestructured enterprises, or work in the informal sector, or resort to subsistence agriculture. Thus, underemployment in the CIS is a mirror image of unemployment in the European transition economies. Accordingly, the high employment-to-population ratios in many CIS countries do not necessarily signify favorable labor market performance. Instead they often indicate delayed enterprise restructuring, the maintenance of unsustainable jobs in uncompetitive firms, and the existence of a large informal sector as an employer of last resort. Labor market segmentation has been caused by a sharp increase in earnings differentials and the attendant increase in the incidence of low-paid jobs, by the polarization of regional labor market conditions, and finally by the growth of the informal sector offering casual, low-productivity jobs. Labor market segmentation and accompanying inequalities are more pronounced in the CIS than in the European transition economies.